Intramolecular electron transfer and charge delocalization in bistable donor–acceptor systems based on perchlorotriphenylmethyl radicals linked to ferrocene and tetrathiafulvalene units. (17th March 2014) - Souto, Manuel; Morales, Dayana C.; Guasch, Judith; Ratera, Imma; Rovira, Concepció; Painelli, Anna; Veciana, Jaume
<x xml:space="preserve">Abstract</x> A comparative analysis of the physicochemical properties of different donor–acceptor dyads, based on a perchlorotriphenylmethyl radical acceptor subunit linked through a vinylene π‐bridge to ferrocene derivatives (1–3) or a tetrathiafulvalene (4) donor subunit, is presented. Intramolecular electron transfer and charge delocalization of these donor–acceptor dyads are discussed on the basis of data obtained in solution by cyclic voltammetry, UV–Vis near‐infrared, and electron spin resonance spectroscopies. Bistability in the crystalline phase is also discussed on the basis of the results provided by X‐ray diffraction analysis and temperature‐dependent Mössbauer spectra. Copyright © 2014 John Wiley & Sons, Ltd.